Testing C4.5 Algorithm Using Rapid Miner Applications In Determining Customer Satisfaction Levels - Fithrie Soufitri; Ellanda Purwawijaya; Eka Hayana Hasibuan; Roy Nuary Singarimbun (Sean Institute, 2021)
Data mining is a series of processes to extract added value in the form of information that has not been known manually from a database. The resulting information is obtained by extracting and recognizing important or interesting patterns from the data contained in the database. One part of the service of an agency is the service to customers, customers or those related to certain services. The quality of service is assessed by what has been done and how to treat from those who serve, some provisions used to ensure service optimization are Confiden, Integrity, Pride and Passion with the main purpose or output is Customer Satisfaction. The process of Forming a Pattern of Satisfaction Level by Utilizing the C4.5 Algorithm Penelitain process is carried out by data collection, testing with applications, exposure of pattern results or Knowledge. Pola yang terbentuk after the extraction is 1.Integrity = low: quite satisfied very satisfied=0, quite satisfied=3Integrity = tall, Passion = low: quite satisfied very satisfied =0, quite satisfied =2, Passion = tall: very satisfied very satisfied =11, quite satisfied =0.